The grammar of repetition : Nupe grammar at the syntax-phonology interface - Kandybowicz, Jason (Linguistik aktuell ;, 2008)
Displacement is a fundamental property of grammar. Typically, when an occurrence moves it is pronounced in only one environment. This was previously viewed as a primitive/irreducible property of grammar. Recent work, however, suggests that it follows from principled interactions between the syntactic and phonological components of grammar. As such, the phonetic character of movement chains can be seen as both a reflection of and probe into the syntax-phonology interface. This volume deals with repetition, an atypical outcome of movement operations in which displaced elements are pronounced mul.